INNV-06. TREATMENT RESPONSE TO BEVACIZUMAB OVER TWO YEARS IN A PATIENT WITH GENETICALLY PROVEN SOMATIC NEUROFIBROMATOSIS TYPE 2 MOSAICISM. (11th November 2019) - Basenach, Elena; Förster, Alisa; Raab, Peter; Alzein, Samer; Schmidt, Gunnar; Krauss, Joachim; Heidenreich, Fedor; Hartmann, Christian; Auber, Bernd; Wiese, Bettina; Weber, Ruthild
Abstract: Neurofibromatosis type 2 (NF2) is a tumor predisposition syndrome characterized by the development of schwannomas, especially bilateral vestibular schwannomas (VS), and meningiomas. Heterozygous pathogenic variants in the NF2 gene are known to cause NF2, whereby somatic mosaicism is present in 25% of simplex patients. In schwannomatosis, a disorder phenotypically similar to NF2, heterozygous SMARCB1 or LZTR1 variants may be causative. Recently, bevacizumab has shown efficiency as therapy for VS in some NF2 patients. We report on a thirty-three-year-old patient with bilateral VS, fourteen additional schwannomas and one intracranial meningioma. Next generation sequencing using a cancer gene panel and Sanger sequencing of LZTR1 on blood and oral mucosa DNA revealed no pathogenic variants in NF2, SMARCB1 or LZTR1 . Sanger sequencing on DNA from three schwannomas identified the known NF2 nonsense variant c.784C >T;p.(R262*) (NM_000268.3, GRCh37/hg19) in all tumors, leading to the diagnosis of somatic NF2 mosaicism. Because of hearing impairment and tumor progression the patient underwent an off-label therapy with 5mg/kg bevacizumab. To determine treatment response, we evaluated MRI scans from five pre-therapeutic and two therapeutic years as well as pure-tone audiometry. After 25 months of treatment, (i) the pure-tone average improved by 11.2 dB indicating a hearing benefit, (ii) four of seven non-vestibular schwannomas showed a volume reduction of ≥ 20%, (iii) the volume of three of seven schwannomas stabilized, and (iv) the growth rate of the meningioma decreased. In conclusion, in a patient with somatic NF2 mosaicism, an off-label therapy with bevacizumab was efficient with respect to hearing improvement and tumor shrinkage in over half of non-vestibular schwannomas over a period of two years.